Autofahren um jeden Preis? Wie private Haushalte auf Änderungen der Kraftstoffpreise reagieren. - Hautzinger, Heinz; Haag, Günter; Helms, Maja; Hugo, Joachim (Deutscher Verkehrs-Verl., 2005)
Immer wieder wird die Frage kontrovers diskutiert, welchen Einfluss die Höhe des Kraftstoffpreises auf das Mobilitätsverhalten vor allem privater Haushalte hat. Dies betrifft die Wirkungen der Ökosteuer, aber auch andere Ereignisse wie z.B. die von Marktprozessen. Der Artikel fasst die Ergebnisse einer entsprechenden Studie zur Preiselastizität der Verkehrsnachfrage privater Haushalte zusammen. Erstmals konnten neben makroökonomischen Zeitreihen auch die Mikrodaten des Mobilitätspanels herangezogen werden. difu

The study presented here - based on a project carried out on behalf of the Ministry of Transport, Building and Construction and Housing - features empirically-proven facts about the impact of fuel price increases on the mobility behaviour of private car owners. The results of this investigation can be summarized as follows: 1) Any decrease in private car users' transport demand - prompted by fuel price rises - is disproportionately low; price elasticity is minimal. 2) One of the reasons for this disproportionately low decrease in car use is the relative growth in earnings of most car owners, which allows for more money to be spent on remaining mobile. 3) Private car owners react to changes in fuel prices differently when buying new cars since they tend to opt for cars running on diesel petrol and not to ad just their way of using the car. 4) Fuel price rises induced by the state appear to have a greater impact than those caused by changes in market conditions. 5) Reduced car use due to fuel price in creases tends not to create any extra demand or public transport. difu
Keywords: Individualverkehr; Autoverkehr; Privater Haushalt; Untersuchung; Modellrechnung; Verkehrsmittelwahl; Verkehrsverhalten; Verkehrsnachfrage; Benzinpreis; Mobilitätsverhalten; Verkehrsforschung